1998
DOI: 10.1007/s004010050835
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopic localization of anti-myelin-associated glycoprotein autoantibodies in a patient with peripheral neuropathy initially lacking a detectable IgM gammopathy

Abstract: We report here on a patient with anti-myelin-associated glycoprotein (MAG) neuropathy in whom examination of a sural nerve biopsy by multichannel confocal microscopy showed a partly overlapping distribution of MAG and IgM deposits in myelinated fibers. Our data demonstrate that MAG in Schmidt-Lanterman incisures and paranodal loops, as well as some additional HNK-1-positive components of the basal lamina, are the major targets of the anti-MAG monoclonal IgM autoantibodies in this neuropathy in vivo. Perforatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…25 However, we observed in this study IgM deposits not strictly colocalized with MAG, particularly on the basement membrane of the Schwann cells and in compact myelin. These results confirmed previous studies 3,18 showing that anti-MAG IgM antibodies are directed against additional molecules involving other HNK-1-containing components of the basement membrane of myelinating Schwann cells. These HNK-1-containing epitopes could belong to fibronectin, L1, J1/ tenascin, 16 some integrins 19 or sulfoglucuronyl, 12 and chondroitin sulfate proteoglycans.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…25 However, we observed in this study IgM deposits not strictly colocalized with MAG, particularly on the basement membrane of the Schwann cells and in compact myelin. These results confirmed previous studies 3,18 showing that anti-MAG IgM antibodies are directed against additional molecules involving other HNK-1-containing components of the basement membrane of myelinating Schwann cells. These HNK-1-containing epitopes could belong to fibronectin, L1, J1/ tenascin, 16 some integrins 19 or sulfoglucuronyl, 12 and chondroitin sulfate proteoglycans.…”
Section: Discussionsupporting
confidence: 94%
“…23 The role of the anti-MAG antibodies as the main pathogenic factor in the neuropathy has been confirmed by several studies. Gabriel et al 3 recently demonstrated by confocal microscopy that IgM antibody deposits were associated with sites of MAG localization, mainly Schmidt Lanterman incisures and paranodal loops. IgM deposits were additionally localized in the basal lamina of myelin-forming Schwann cells.…”
mentioning
confidence: 97%
“…Valldeoriola et al 22 described a patient with CIDP who initially was negative for IgM anti-MAG antibody but who developed IgM M-protein and anti-MAG antibody activity 2 years later. Some may later develop IgM gammopathy, 11 whereas patients lacking a verifiable IgM gammopathy may have polyneuropathy associated with IgM anti-MAG antibody. 19,23 Patients 4 and 11 (Table 1) without M-protein had very high IgM anti-SGPG antibody titers, IgMs from whom strongly reacted with MAG.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical investigations of nerve biopsies from such patients demonstrate a selective loss of MAG in many fibers and suggest an important role for the MAG antigen in incisures and paranodal loops. 44,45 However, the induction of neurological signs in rats by immunization with SGPG, as mentioned earlier, suggests that the cross-reacting glycolipid antigens may be very important, because rats do not contain the reactive carbohydrate epitope on myelin proteins but do express low levels of SGPG. The binding of anti-SGPG antibodies to endothelial cells has been suggested to be involved in breakdown of the blood-nerve barrier in these patients.…”
Section: Pathogenic Mechanisms In Neuropathies Associated With Antibomentioning
confidence: 96%